The efficacy of pegylated interferon alpha 2a or 2b plus ribavirin in chronic hepatitis C patients - Necati YENİCE; Özgür MEHTAP; Mübeccel GÜMRAH; Nurten ARICAN (Turkish Journal of Gastroenterology, 2019)
-